Block polymer containing sulfoxide structure as well as preparation method and application of block polymer
By developing block polymers containing sulfoxide structures, using their interaction with drugs and polyethylene glycol structures to form efficient drug-carrying micelles, the problem of water solubility of hydrophobic drugs is solved, and drug-carrying capacity is improved. The efficacy reduces toxicity and cost and has excellent clinical application prospects.
Patent Information
- Application Number
- CN202411266216.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-20
AI Technical Summary
In the prior art, the water solubility problem of hydrophobic drugs is difficult to solve, resulting in limited efficacy of the drug, high toxic side effects, and low drug-carrying efficiency of carriers, which limits its clinical application.
Develop a block polymer containing sulfoxide structure, which interacts with the drug through the interaction of sulfoxide groups to form loose cohesive cores, improves the drug carrying capacity and compatibility of drugs, and uses polyethylene glycol structure to provide hydrophilicity and form efficient drug-carrying micelles.
It significantly improves the drug carrying capacity and efficacy of hydrophobic drugs, reduces toxicity and cost, improves the maximum tolerated dose of drugs, enhances the stability and safety of drug-loading micelles, and has excellent clinical application prospects.
Smart Images

Figure CN119161547A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedicine technology, and in particular to a block polymer containing a sulfoxide structure, a preparation method and application thereof. Background Art
[0002] Small molecule drugs have unique advantages, such as clear structure, clear target, low cost, etc., but it is undeniable that they also have many defects, such as limited efficacy, high toxicity and side effects, and about 40% of clinically approved drugs and 90% of preclinical candidate drugs are hydrophobic, which is difficult to administer systemically. In clinical or preclinical studies, in order to solve the water solubility problem of hydrophobic drugs so that they can be administered systemically, surfactants such as Span, Tween, polyethylene glycol 400 (PEG400) or organic solvents such as dimethyl sulfoxide (DMSO) are often used for solubilization, but these surfactants have limited solubilization effects and have certain toxic side effects. Taking the first-generation taxane drug paclitaxel (PTX) as an example, the ethanol and polyoxyethylene castor oil in its ingredients bring greater immunogenicity and allergic reactions, resulting in greater toxicity and side effects in clinical practice, limited dosage and inability to ensure continuity of treatment. Therefore, the development of new solubilization materials or delivery technologies to improve the solubility of drugs and improve their in vivo efficacy has important significance and market value.
[0003] Nano drug delivery technology represented by polymer carrier materials such as polylactic acid (PLA), polycaprolactone (PCL) or polylactic-glycolic acid (PLGA) can significantly improve the solubility of hydrophobic drugs, improve their pharmacokinetics, and reduce their accumulation in non-target organs, thereby significantly reducing toxic side effects and improving the quality of life of patients. However, this method still has defects such as low carrier drug loading efficiency. Taking polymer micelle system as an example, its drug loading is usually less than 10%, and some drugs are even less than 1%, which greatly limits its clinical application. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a block polymer containing a sulfoxide structure, a preparation method and application thereof, and a drug-loaded micelle. The block polymer containing a sulfoxide structure provided by the present invention has a high drug-loading capacity.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a block polymer containing a sulfoxide structure, which has a structure shown in Formula I:
[0007]
[0008] In formula I, n is 5 to 100, m is 20 to 500, R1 is hydrogen or methyl, and x is 1 to 8;
[0009] The structure of the block polymer containing a sulfoxide structure also includes a residue from a chain transfer agent.
[0010] Preferably, in formula I, R1 is hydrogen.
[0011] Preferably, the specific structure is as shown in Formula I-1:
[0012]
[0013] The present invention also provides a method for preparing the block polymer containing a sulfoxide structure described in the above technical solution, comprising the following steps:
[0014] The first reaction is carried out between mercaptoethanol and 1-bromobutane to obtain a compound represented by Formula 1;
[0015]
[0016] The compound represented by Formula 1 is subjected to a second reaction with the compound represented by Formula 2 to obtain an acrylic acid ester-containing thioether monomer represented by Formula 3;
[0017]
[0018] The acrylate-containing thioether monomer and hydrogen peroxide are subjected to a third reaction to obtain an acrylate-containing sulfoxide monomer as shown in Formula 4;
[0019]
[0020] The sulfoxide monomer containing acrylate is subjected to free radical polymerization reaction under the action of polyethylene glycol macromolecular chain transfer agent to obtain the block polymer containing sulfoxide structure.
[0021] Preferably, the reagents for the first reaction further include a first acid binding agent and a first organic solvent;
[0022] The first acid binding agent includes one or more of potassium carbonate, triethylamine, N,N-diisopropylethylamine and pyridine;
[0023] The first organic solvent includes one or more of acetonitrile, dichloromethane and chloroform;
[0024] The molar ratio of the 1-bromobutane to the mercaptoethanol is 1 to 1.5:1;
[0025] The molar ratio of the first acid binding agent to mercaptoethanol is 1 to 2:1;
[0026] The temperature of the first reaction is room temperature and the time is 12 to 24 hours.
[0027] Preferably, the reagents for the second reaction further include a second acid binding agent and a second organic solvent;
[0028] The second acid binding agent includes one or more of triethylamine, N,N-diisopropylethylamine and pyridine;
[0029] The second organic solvent includes one or more of diethyl ether, dichloromethane and chloroform;
[0030] The molar ratio of the compound represented by Formula 2 to the compound represented by Formula 1 is 1 to 1.5:1;
[0031] The ratio of the amount of the second acid binding agent to the compound represented by Formula 1 is 1 to 2:1;
[0032] The temperature of the second reaction is room temperature, and the time is 2 to 24 hours.
[0033] Preferably, the reagents for the third reaction further include a catalyst and a third solvent;
[0034] The catalyst includes molybdenum dioxide dichloride;
[0035] The third solvent includes one or more of acetonitrile, acetone and water;
[0036] The molar ratio of the catalyst to the sulfide monomer containing acrylate is 0.01 to 0.1:1;
[0037] The molar ratio of the hydrogen peroxide to the acrylate-containing thioether monomer is 1 to 1.1:1;
[0038] The temperature of the third reaction is room temperature, and the time is 20 to 60 minutes.
[0039] Preferably, the polyethylene glycol macromolecular chain transfer agent includes a compound having a structure shown in Formula 5:
[0040]
[0041] The reagents for the free radical polymerization reaction also include a free radical initiator and a fourth organic solvent;
[0042] The free radical initiator includes azo initiators, organic peroxide initiators and inorganic peroxide initiators;
[0043] The fourth organic solvent includes N,N-dimethylformamide, dioxane or dimethyl sulfoxide;
[0044] The molar ratio of the acrylate-containing sulfoxide monomer to the free radical initiator is 1:0.0025-0.1;
[0045] The molar ratio of the acrylate-containing sulfoxide monomer to the polyethylene glycol macromolecular chain transfer agent is 1:0.01-0.2;
[0046] The temperature of the free radical polymerization reaction is 60-80° C., the time is 6-24 hours, and the free radical polymerization reaction is carried out in anhydrous and oxygen-free state.
[0047] The present invention also provides the use of the block polymer containing a sulfoxide structure described in the above technical solution or the block polymer containing a sulfoxide structure obtained by the preparation method described in the above technical solution in solubilizing hydrophobic drugs and preparing hydrophobic drug carriers, wherein the oil-water partition coefficient of the hydrophobic drug is greater than 2, and the molecular weight of the hydrophobic drug is 150-1500.
[0048] The present invention also provides a drug-loaded micelle, which is prepared by a thin film dispersion method, a nanoprecipitation method or a microfluidic method using the block polymer containing a sulfoxide structure described in the above technical solution or the block polymer containing a sulfoxide structure obtained by the preparation method described in the above technical solution and a hydrophobic drug.
[0049] The present invention provides a block polymer containing a sulfoxide structure having a structure shown in Formula I:
[0050]
[0051] The block polymer containing sulfoxide structure of the present invention contains sulfoxide structure, and liquid-liquid phase separation occurs under physiological conditions to form condensate droplets; the sulfoxide structure is combined with the polyethylene glycol structure to form an amphiphilic block polymer (wherein, the hydrophobic block is a polymer containing sulfoxide groups, and the hydrophilic block is polyethylene glycol (PEG)), so that the block polymer containing sulfoxide structure of the present invention can form a condensate core with a loose structure. Compared with traditional drug-loaded micelles, the micelles formed by the block polymer containing sulfoxide structure of the present invention have a loose condensate core, which can accommodate more drugs in space and can increase the drug loading. At the same time, based on the universal solvent properties of dimethyl sulfoxide, the sulfoxide group in the block polymer containing sulfoxide structure can provide good polymer-drug compatibility, and the side chain fatty chain promotes the interaction between the block polymer containing sulfoxide structure and the drug molecule, so the block polymer containing sulfoxide structure can solubilize common hydrophobic drugs and efficiently deliver them to the body. In addition, the block polymer containing sulfoxide structure is expected to be developed into a universal solubilizer and drug delivery carrier for hydrophobic small molecule drugs to improve drug solubility, reduce toxicity, increase the maximum tolerated dose (MTD) of drugs, and improve efficacy, etc. In addition, the carrier has good biocompatibility and safety, so it has excellent clinical application prospects.
[0052] The improved drug loading capacity of the block polymer containing a sulfoxide structure of the present invention has the following advantages: (1) For systemic administration, the improved drug loading capacity of the block polymer containing a sulfoxide structure will reduce the amount of the block polymer containing a sulfoxide structure as a carrier material, which can reduce costs and reduce safety issues of the block polymer containing a sulfoxide structure as a carrier material, such as the burden on patients caused by the degradation, metabolism and excretion of the block polymer containing a sulfoxide structure as a carrier material. (2) In order to achieve the drug therapeutic window, a high drug loading capacity means a low concentration of drug-loaded micelles during administration, which will improve the stability of the drug-loaded micelles on the one hand, and ensure the appropriate viscosity of the solution on the other hand, which is convenient for intravenous injection. (3) The block polymer containing a sulfoxide structure with a high drug loading capacity has high compatibility with drugs, making the drug-loaded micelles stable, avoiding various problems such as unexpected drug release and aggregation, and promoting material safety and efficacy.
[0053] Compared with the prior art, the present invention has the following beneficial effects:
[0054] (1) The block polymer containing sulfoxide structure provided by the present invention has excellent solubilization ability for existing hydrophobic drugs, and its solubilization ability is significantly better than that of existing surfactants, which can greatly reduce the use of organic solvents. Therefore, it can help some hydrophobic drugs that cannot be effectively dissolved to verify their in vivo effects, which has great research significance.
[0055] (2) The block polymer containing sulfoxide structure provided by the present invention has a significantly better drug loading capacity for hydrophobic drugs than commercial polymer delivery carriers, such as PEG-PDLLA (polyethylene glycol-poly-DL-lactide), PEG-PLGA (polyethylene glycol-polylactic acid-glycolic acid), PEG-PCL (polyethylene glycol-polycaprolactone), etc., and exhibits higher stability than commercial delivery carriers in physiological environment. The in vivo efficacy has also been proven to have outstanding efficacy and excellent safety performance, and therefore has outstanding clinical application prospects.
[0056] The present invention also provides a method for preparing the block polymer containing a sulfoxide structure described in the above technical solution. The preparation method provided by the present invention is simple to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of BuSEA obtained in Example 1;
[0058] Figure 2 The H NMR spectrum and GPC spectrum of PEG-PBuSEA obtained in Example 1;
[0059] Figure 3 The H NMR spectrum and GPC spectrum of PBuSEA obtained in Example 2;
[0060] Figure 4 This is a characterization diagram of the properties of the PBuSEA condensate droplets obtained in Test Example 1;
[0061] Figure 5 The particle size and electron microscopy image of micelle PEG-PBuSEA in Test Example 2;
[0062] Figure 6 It is a characterization diagram of the compatibility of PEG-PBuSEA and PEG-PDLLA with drugs in Test Example 3;
[0063] Figure 7 The stability characterization diagram of PEG-PBuSEA and PEG-PDLLA encapsulating paclitaxel and MZ-1 in Test Example 4;
[0064] Figure 8 This is a diagram of the cytotoxicity experiment of PEG-PBuSEA in Test Example 5;
[0065] Fig. 9 This is a diagram showing the tumor inhibition effect of PEG-PBuSEA@PTX drug-loaded micelles in Test Example 6 in the mouse triple-negative breast cancer (MDB-MA-231) subcutaneous tumor model. DETAILED DESCRIPTION
[0066] The present invention provides a block polymer containing a sulfoxide structure, which has a structure shown in Formula I:
[0067]
[0068] In formula I, n is 5 to 100, m is 20 to 500, R1 is hydrogen or methyl, and x is 1 to 8;
[0069] The structure of the block polymer containing a sulfoxide structure also includes a residue from a chain transfer agent.
[0070] In the present invention, the value of n can be 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95 or 100. In the present invention, the value of m can be 20, 50, 70, 80, 100, 113, 120, 150, 180, 200, 220, 250, 280, 300, 320, 350, 380, 400, 430, 450, 470 or 500. In a specific embodiment of the present invention, in the block polymer containing sulfoxide structure, the molecular weight of the sulfoxide structure-containing polymer block is preferably 12000, that is, n≈60; the molecular weight of the polyethylene glycol block is preferably 5000, that is, m≈113.
[0071] In the present invention, in formula I, R1 is preferably hydrogen.
[0072] The present invention does not specifically limit the type of the residue, as long as it is consistent with the group of the chain transfer agent in the preparation process.
[0073] In a specific embodiment of the present invention, the specific structure of the block polymer containing a sulfoxide structure is preferably as shown in Formula I-1:
[0074]
[0075] The principle that the block polymer containing a sulfoxide structure provided by the present invention has a high drug loading capacity is that: (1) the compatibility between the block polymer containing a sulfoxide structure and the drug is improved by interacting with the drug through the sulfoxide group; and (2) the micelles formed by assembling the block polymer containing a sulfoxide structure have a loose aggregate core, which provides sufficient drug loading space.
[0076] The present invention also provides a method for preparing the block polymer containing a sulfoxide structure described in the above technical solution, comprising the following steps:
[0077] The first reaction is carried out between mercaptoethanol and 1-bromobutane to obtain a compound represented by Formula 1;
[0078]
[0079] The compound represented by Formula 1 is subjected to a second reaction with the compound represented by Formula 2 to obtain an acrylic acid ester-containing thioether monomer represented by Formula 3;
[0080]
[0081] The acrylate-containing thioether monomer and hydrogen peroxide are subjected to a third reaction to obtain an acrylate-containing sulfoxide monomer as shown in Formula 4;
[0082]
[0083] The sulfoxide monomer containing acrylate is subjected to free radical polymerization reaction under the action of polyethylene glycol macromolecular chain transfer agent to obtain the block polymer containing sulfoxide structure.
[0084] In the present invention, unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.
[0085] The present invention conducts a first reaction between mercaptoethanol and 1-bromobutane to obtain a compound shown in Formula 1;
[0086]
[0087] In the present invention, the reagent of the first reaction preferably also includes a first acid binding agent and a first organic solvent. In the present invention, the first acid binding agent preferably includes one or more of potassium carbonate, triethylamine, N,N-diisopropylethylamine and pyridine, and is more preferably potassium carbonate. In the present invention, the first organic solvent preferably includes one or more of acetonitrile, dichloromethane and chloroform, and is more preferably acetonitrile, and is more preferably anhydrous acetonitrile.
[0088] In the present invention, the molar ratio of the 1-bromobutane to the mercaptoethanol is preferably 1 to 1.5:1, specifically 1:1, 1.1:1, 1.11:1, 1.2:1, 1.3:1, 1.4:1 or 1.5:1.
[0089] In the present invention, the molar ratio of the first acid binding agent to mercaptoethanol is preferably 1 to 2:1, specifically 1:1, 1.2:1, 1.5:1, 1.56:1, 1.8:1 or 2:1.
[0090] In the present invention, the temperature of the first reaction is preferably room temperature, and the time is preferably 12 to 24 hours. In the present invention, during the first reaction, it is preferred to detect whether the 1-bromobutane has reacted completely by a spot plate, and when the 1-bromobutane has reacted completely, the first reaction ends.
[0091] After the first reaction, the present invention preferably further comprises: filtering the obtained first reaction liquid to collect the filtrate; concentrating the filtrate under reduced pressure to obtain a viscous substance; and performing column chromatography on the viscous substance to obtain the compound represented by Formula 1. In the present invention, the eluent for the column chromatography is preferably a mixed solvent of n-hexane and ethyl acetate in a volume ratio of 1:1.
[0092] After obtaining the compound of Formula 1, the present invention conducts a second reaction between the compound of Formula 1 and the compound of Formula 2 to obtain an acrylic acid ester-containing thioether monomer of Formula 3;
[0093]
[0094] In the present invention, the reagent of the second reaction preferably also includes a second acid binding agent and a second organic solvent. In the present invention, the second acid binding agent preferably includes one or more of triethylamine, N,N-diisopropylethylamine and pyridine, and more preferably triethylamine. In the present invention, the second organic solvent preferably includes one or more of ether, dichloromethane and chloroform, and more preferably dichloromethane, and more preferably anhydrous dichloromethane.
[0095] In the present invention, R1 in the compound represented by Formula 2 may be hydrogen or methyl. In a specific embodiment of the present invention, R1 is preferably hydrogen.
[0096] In the present invention, the molar ratio of the compound represented by Formula 2 to the compound represented by Formula 1 is preferably 1 to 1.5:1, specifically 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1 or 1.5:1.
[0097] In the present invention, the molar ratio of the second acid binding agent to the compound represented by Formula 1 is preferably 1 to 2:1, specifically 1:1, 1.2:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1 or 2:1.
[0098] In the present invention, the temperature of the second reaction is preferably room temperature, and the time is preferably 2 to 24 hours.
[0099] In the present invention, the second reaction of the compound of formula 1 and the compound of formula 2 preferably comprises the following steps: dissolving the compound of formula 1 and the second acid binding agent in a second organic solvent to obtain a solution of the compound of formula 1; dissolving the compound of formula 2 in a second organic solvent to obtain a solution of the compound of formula 2; and dripping the solution of the compound of formula 2 into the solution of the compound of formula 1 to perform the second reaction. In the present invention, the temperature of the dripping process is preferably 0 to 5°C. In the present invention, the time of the second reaction starts from the completion of the dripping of the solution of the compound of formula 2.
[0100] After the second reaction, the present invention preferably further comprises: filtering the obtained second reaction liquid, collecting the filtrate; washing, drying, concentrating under reduced pressure and purifying the filtrate on a silica gel column in sequence to obtain the sulfide monomer containing acrylate shown in Formula 3. In the present invention, the washing preferably comprises washing with a saturated sodium bicarbonate solution, washing with hydrochloric acid and washing with saturated sodium chloride in sequence; the number of washings with a saturated sodium bicarbonate solution, washing with hydrochloric acid and washing with saturated sodium chloride is preferably 1 time, and the concentration of hydrochloric acid in the hydrochloric acid washing is preferably 1 mol / L. In the present invention, the drying method is preferably drying with a desiccant, and the desiccant is preferably anhydrous magnesium sulfate. In the present invention, the eluent for the silica gel column purification is preferably a mixed solvent of n-hexane and ethyl acetate in a volume ratio of 10:1.
[0101] After obtaining the acrylate-containing thioether monomer shown in Formula 3, the present invention conducts a third reaction between the acrylate-containing thioether monomer and hydrogen peroxide to obtain the acrylate-containing sulfoxide monomer shown in Formula 4;
[0102]
[0103] In the present invention, the reagent of the third reaction preferably also includes a catalyst and a third solvent. In the present invention, the catalyst preferably includes molybdenum dioxide dichloride. In the present invention, the third solvent preferably includes one or more of acetonitrile, acetone and water, and is further preferably acetonitrile.
[0104] In the present invention, the molar ratio of the catalyst to the acrylate-containing thioether monomer is preferably 0.01 to 0.1:1, specifically 0.01:1, 0.015:1, 0:02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1 or 0.1:1.
[0105] In the present invention, the molar ratio of the hydrogen peroxide to the acrylate-containing thioether monomer is preferably 1 to 1.1:1, specifically 1:1, 1.05:1 or 1.1:1. In the present invention, the hydrogen peroxide is preferably used in the form of hydrogen peroxide, and the mass fraction of the hydrogen peroxide is preferably 30%.
[0106] In the present invention, the temperature of the third reaction is preferably room temperature, and the time is preferably 20 to 60 minutes.
[0107] In the present invention, the third reaction preferably comprises the following steps: dissolving the thioether monomer containing acrylate in a third solvent to obtain a thioether monomer solution; sequentially adding a catalyst and dropping hydrogen peroxide into the thioether monomer solution to perform the third reaction. In the present invention, the dropping temperature of the hydrogen peroxide is preferably an ice water bath.
[0108] After the third reaction, the present invention preferably further comprises: concentrating the obtained third reaction liquid under reduced pressure to obtain a viscous substance; and purifying the viscous substance by column chromatography to obtain an acrylate-containing sulfoxide monomer shown in Formula 4. In the present invention, the eluent for column chromatography purification is preferably a mixed solvent of dichloromethane and methanol in a volume ratio of 20:1.
[0109] After obtaining the sulfoxide monomer containing acrylate as shown in Formula 4, the present invention subjects the sulfoxide monomer containing acrylate to free radical polymerization under the action of a polyethylene glycol macromolecular chain transfer agent to obtain the block polymer containing the sulfoxide structure.
[0110] In the present invention, the polyethylene glycol macromolecular chain transfer agent preferably includes a compound having a structure shown in Formula 5:
[0111]
[0112] In the present invention, the reagent of the free radical polymerization reaction preferably also includes a free radical initiator and a fourth organic solvent. In the present invention, the free radical initiator preferably includes an azo initiator, an organic peroxide initiator or an inorganic peroxide initiator, and is more preferably an azo initiator. In the present invention, the azo initiator preferably includes one or more of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN) and dimethyl azobisisobutyrate (AIBME), and is more preferably azobisisobutyronitrile (AIBN). In the present invention, the organic peroxide initiator preferably includes one or more of dicarbonate peroxide, acyl peroxide and ester peroxide; the dicarbonate peroxide preferably includes diisopropyl peroxydicarbonate and / or dicyclohexyl peroxydicarbonate; the acyl peroxide preferably includes benzoyl peroxide and / or lauroyl peroxide; the ester peroxide preferably includes tert-butyl perbenzoate and / or tert-butyl peroxyvalerate. In the present invention, the inorganic peroxy initiator preferably includes persulfate, and the persulfate preferably includes one or more of potassium persulfate, sodium persulfate and ammonium persulfate.
[0113] In the present invention, the fourth organic solvent preferably includes N,N-dimethylformamide (DMF), dioxane or dimethyl sulfoxide, and more preferably is N,N-dimethylformamide (DMF).
[0114] In the present invention, the molar ratio of the acrylate-containing sulfoxide monomer to the free radical initiator is preferably 1:0.0025-0.1, and specifically can be 1:0.0025, 1:0.005, 1:0.0056, 1:0.006, 1:0.007, 1:0.008, 1:0.009, 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09 or 1:0.1.
[0115] In the present invention, the molar ratio of the acrylate-containing sulfoxide monomer to the polyethylene glycol macromolecular chain transfer agent is 1:0.01-0.2, specifically 1:0.01, 1:0.017, 1:0.02, 1:0.05, 1:0.08, 1:0.1, 1:0.15 or 1:0.2.
[0116] In the present invention, the temperature of the free radical polymerization reaction is preferably 60-80°C, the time is preferably 6-24 hours, and the free radical polymerization reaction is preferably carried out in anhydrous and oxygen-free state. In the present invention, the free radical polymerization reaction is preferably carried out in an oil bath.
[0117] After the free radical polymerization reaction, the present invention preferably further comprises: terminating the reaction, subjecting the obtained reaction liquid to ice ethanol precipitation, and subjecting the obtained filtrate to reduced pressure drying to obtain the block polymer containing the sulfoxide structure. In the present invention, the termination reaction is preferably performed by liquid nitrogen quick freezing.
[0118] In the present invention, the preparation process of the block polymer containing sulfoxide structure is as follows:
[0119]
[0120] The present invention also provides the use of the block polymer containing a sulfoxide structure described in the above technical solution or the block polymer containing a sulfoxide structure obtained by the preparation method described in the above technical solution in solubilizing hydrophobic drugs and preparing hydrophobic drug carriers, wherein the oil-water partition coefficient of the hydrophobic drug is greater than 2, and the molecular weight of the hydrophobic drug is 150-1500.
[0121] In the present invention, the hydrophobic drug preferably includes a proteolytic targeting chimera, a quinoline drug, ketoconazole, ticagrelor, cardotril, dabigatran, bifonazole, permethrin, a sartan drug, clotrimazole, vitamin K4, rifaximin, a taxane chemotherapy drug, doxorubicin, lansoprazole, a dipine drug, curcumin, verapamil, estradiol benzoate, vitamin K1, reserpine, gemfibrozil, diltiazem, terbinafine, sorafenib, lurasidone or palm chloramphenicol. In the present invention, the proteolytic targeting chimera preferably includes MZ-1, LC-2 or PROTAC 3 based on gefitinib. In the present invention, the quinoline drug preferably includes chloroquine. In the present invention, the sartan drug preferably includes irbesartan, the taxane chemotherapy drug preferably includes paclitaxel or docetaxel, and the dipine drug preferably includes nifedipine.
[0122] The present invention also provides a drug-loaded micelle, which is prepared by a thin film dispersion method, a nanoprecipitation method or a microfluidic method using the block polymer containing a sulfoxide structure described in the above technical solution or the block polymer containing a sulfoxide structure obtained by the preparation method described in the above technical solution and a hydrophobic drug.
[0123] In the present invention, the thin film dispersion method preferably comprises the following steps:
[0124] The block polymer containing sulfoxide structure and the drug are dissolved in an organic solvent, and the obtained mixture is subjected to rotary evaporation to obtain a rotary evaporation product; the rotary evaporation product is mixed with water, and hydration, ultrasound and centrifugation are performed in sequence to obtain the drug-loaded micelles.
[0125] In the present invention, the organic solvent preferably includes ethanol. The present invention does not specifically limit the dosage ratio of the block polymer containing sulfoxide structure and the drug, and can be set according to actual needs. In the present invention, the dosage ratio of the rotary evaporator and water is preferably 0.5-20 mg: 1 mL. In the present invention, the hydration temperature is preferably 20-50°C, and the time is preferably 1-10 min. In the present invention, the power of the ultrasound is preferably 120W, and the time is preferably 1-15 min. In the present invention, the gravitational acceleration of the centrifugation is preferably 5000g. After the centrifugation, the present invention also includes ultrafiltration to remove free drugs to obtain the drug-loaded micelles; the drug-loaded micelles are preferably in the form of a drug-loaded micelle dispersion.
[0126] In the present invention, the nanoprecipitation method preferably comprises the following steps: dissolving the drug and the block polymer containing sulfoxide structure in a benign solvent to obtain an organic phase; under stirring, dropping the organic phase into water, continuing stirring at room temperature, and then dialyzing to obtain the drug-loaded micelles. In the present invention, the benign solvent preferably includes ethanol, dimethyl sulfoxide (DMSO) or N,N-dimethylformamide (DMF). The present invention does not specifically limit the dosage ratio of the block polymer containing sulfoxide structure and the drug, and can be set according to actual needs. In the present invention, the stirring speed is preferably 100 to 1500 rpm. In the present invention, the dripping speed of the organic phase is preferably 1 to 20 mL / min. In the present invention, the time of stirring at room temperature is preferably 2 to 30 min. In the present invention, the molecular weight of the dialysis bag of the dialysis is preferably 3kD to 300kD, and the dialysis can remove the organic solvent and the small molecules that are not encapsulated into the inner core of the micelle. In the present invention, the drug-loaded micelles are preferably present in the form of drug-loaded micelle dispersion.
[0127] In the present invention, the microfluidic method preferably includes the following steps: dissolving the drug and the block polymer containing a sulfoxide structure in a benign solvent to obtain an organic phase; blending the organic phase and water in a microfluidic chip, and dialyzing the obtained blended system to obtain the drug-loaded micelles. In the present invention, the benign solvent preferably includes ethanol, dimethyl sulfone (DMSO) or N,N-dimethylformamide (DMF). The present invention does not specifically limit the dosage ratio of the block polymer containing a sulfoxide structure and the drug, and can be set according to actual needs. In the present invention, during the blending process, the flow rate ratio of the organic phase and water is preferably 3:10 to 1:20. In the present invention, the molecular weight of the dialysis bag of the dialysis is preferably 3kD to 300kD, and the dialysis can remove the organic solvent and the small molecules that are not encapsulated into the inner core of the micelle. In the present invention, the drug-loaded micelles are preferably present in the form of a drug-loaded micelle dispersion.
[0128] The block polymer containing sulfoxide structure provided by the present invention and its preparation method and application are described in detail below in conjunction with the examples, but they should not be construed as limiting the protection scope of the present invention.
[0129] Example 1 Synthesis of PEG-PBuSEA
[0130] Step 1: Add 1-bromobutane (27.2 g, 200 mmol), potassium carbonate (38.6 g, 280 mmol) and 2-mercaptoethanol (14.0 g, 180 mmol) to 200 mL of anhydrous acetonitrile, react overnight, and use a plate to detect whether the reaction of 2-mercaptoethanol is complete. Filter, concentrate the filtrate under reduced pressure, and pass the concentrate through a column with a mixed solvent of n-hexane: ethyl acetate in a volume ratio of 1:1 to obtain a colorless transparent liquid 2-(butylthio)ethanol (22.5 g, yield 91.2%).
[0131] Step 2: Dissolve 2-(butylthio)ethanol (19.4 g, 145 mmol) and triethylamine (22.1 g, 218 mmol) in 250 mL of dichloromethane, add 50 mL of dichloromethane solution containing acryloyl chloride (17.1 g, 189 mmol) dropwise under ice bath conditions, and react at room temperature overnight. Filter, wash the filtrate with saturated sodium bicarbonate solution, 1 mol / L HCl and saturated sodium chloride three times in sequence, dry over anhydrous magnesium sulfate, and concentrate under reduced pressure to obtain a crude product of 2-(butylthio)ethyl acrylate (BuTEA). The crude product was purified by silica gel column (the eluent was a mixed solvent of n-hexane and ethyl acetate in a volume ratio of 10:1) to obtain a colorless transparent liquid BuTEA (15.6 g, yield 57.1%).
[0132] Step 3: BuTEA (3.76 g, 20.0 mmol) was added to 50 mL of acetonitrile, and molybdenum dioxide dichloride (60.0 mg, 0.30 mmol) was added as a catalyst. A 30 wt% hydrogen peroxide solution (2.40 g, 21.2 mmol) was added dropwise under ice bath conditions, and the reaction was carried out at room temperature for 1 h. The reaction solution was concentrated under reduced pressure and quickly passed through a column with a mixed solvent of dichloromethane and methanol in a volume ratio of 20:1 to obtain a colorless liquid BuSEA (3.62 g, yield 90.1%).
[0133] Step 4: 1.2 g (5.88 mmol) of sulfoxide monomer BuSEA, 500 mg (0.1 mmol) of PEG macromolecular RAFT chain transfer agent, and 5.47 mg (0.033 mmol) of AIBN were dissolved in 4 mL of DMF, and the solution was transferred to a polymerization bottle, deoxygenated by nitrogen bubbling for 30 min, placed in a 65°C oil bath for 24 h, and then quickly frozen with liquid nitrogen to terminate the reaction. The product was precipitated with glacial ether and dried under reduced pressure to obtain a light yellow semisolid PEG-PBuSEA (1.60 g, yield 94%).
[0134] The reaction formula of Example 1 is as follows:
[0135]
[0136] Figure 1 The NMR hydrogen spectrum of BuSEA was obtained. The solvent was deuterated chloroform (CDCl3). Figure 1 It can be seen that the target structure is obtained.
[0137] The molecular weight of the obtained PEG-PBuSEA was determined by DMF / LiBr phase GPC.
[0138] Figure 2 The obtained PEG-PBuSEA is shown in Figure 1 as a hydrogen nuclear magnetic resonance spectrum (the solvent is CDCl3) and a gel permeation chromatography spectrum; Figure 2 It can be seen that the target structure is obtained.
[0139] Example 2 Synthesis of PBuSEA
[0140] Step 1: 1 g (4.9 mmol) of sulfoxide monomer BuSEA, 19.8 mg (0.083 mmol) of RAFT chain transfer agent, and 4.55 mg (0.028 mmol) of AIBN were dissolved in 3 mL of DMF, and the mixed solution was transferred to a polymerization bottle, deoxygenated by nitrogen bubbling for 30 min, placed in a 65°C oil bath for 24 h, and then quickly frozen with liquid nitrogen to terminate the reaction. The product was precipitated once with ice ethanol, then precipitated with ice ether, and dried under reduced pressure to obtain a yellow semi-solid PBuSEA (0.91 g, yield 91%).
[0141] The molecular weight of the obtained PBuSEA was measured by DMF / LiBr phase GPC.
[0142] Figure 3 The obtained PBuSEA is shown in Figure 1 as a hydrogen nuclear magnetic resonance spectrum (the solvent is CDCl3) and a gel permeation chromatography spectrum; Figure 3 It can be seen that the target structure is obtained.
[0143] Test Example 1 Characterization of PBuSEA Phase Separation and Aggregate Properties
[0144] PBuSEA was dissolved in dimethyl sulfoxide at a concentration of 100 mg / mL, and then diluted with PBS to a final concentration of 2 mg / mL. The morphology of the condensate droplets was observed by laser confocal microscopy, and its fluid properties were verified by fluorescence bleaching. The fluorescence dye BODIPY for detecting viscosity and the fluorescent dye SBD for detecting polarity were used to obtain the polarity and viscosity information of the condensate droplets based on the changes in their fluorescence lifetime in the droplets.
[0145] The results are as follows Figure 4 As shown, Figure 4 The characterization diagram of the properties of the PBuSEA condensate droplets obtained. Figure 4 In the figure, a is the curve of the turbidity of PBuSEA changing with temperature, b is the droplets of aggregates formed by PBuSEA in different buffers, c is the fluorescence recovery experiment of PBuSEA droplets after photobleaching and FRAP quantitative analysis, and d is the structural formula of the environmentally sensitive fluorescent probe and the pseudo-color image of the polymer containing the fluorescent probe SBD or BODIPY. Figure 4 It can be seen that: PBuSEA begins to form condensate droplets at 16°C in PBS and can exist stably under high serum conditions; through fluorescence bleaching, it was found that the droplets connected to the fluorescent dye tetramethylrhodamine quickly recovered fluorescence, further indicating that it has the fluid properties of condensate droplets; by detecting the fluorescence lifetime of BODIPY and SBD, it was found that compared with the homologous thioether polymer PBuTEA, sulfone polymer PBuSFO, polymer PPeSEA with one carbon chain extended outward, polymer PHeSEA with two carbon chains extended outward, and commercial PDLLA, PBuSEA has the smallest viscosity and the largest polarity, which indicates that the internal space of the condensate droplets is relatively loose and there is sufficient space to accommodate drugs. The strong polarity is also conducive to the dissolution of drugs with polar groups.
[0146] Test Example 2 Characterization of drug loading capacity of block polymer PEG-PBuSEA containing sulfoxide structure
[0147] The drug-loaded micelles were prepared by a thin film dispersion method. 1 mg PEG-PBuSEA and the corresponding drug were dissolved in ethanol or dichloromethane. The organic solvent was rotary evaporated, 1 mL of water was added, and the mixture was hydrated at 20-50°C for 1-10 min. The probe was ultrasonicated (120 W) for 1-15 min, and the aggregated particles were removed by centrifugation at 5000 g. The free drug was then removed by ultrafiltration, and the drug concentration was measured by HPLC. The drug loading LE was calculated as follows: LE = (encapsulated drug mass) / (carrier mass + encapsulated drug mass); the encapsulation efficiency EE was calculated as follows: EE = encapsulated drug mass / fed drug mass, and the micelle particle size was measured by DLS.
[0148] The results are as follows Figure 5 As shown in Tables 1 and 2, Figure 5The particle size and electron microscopy image of micelle PEG-PBuSEA.
[0149] Table 1 Characterization of drug loading, encapsulation efficiency and particle size of micellar PEG-PBuSEA for different drugs
[0150]
[0151]
[0152] Table 2 Drug loading and encapsulation efficiency of PEG-PCL, PEG-PLGA and PEG-PDLLA for different drugs
[0153]
[0154]
[0155] Combination Figure 5 , Table 1 and Table 2, DLS and transmission electron microscopy showed that the particle size of PEG-PBuSEA was about 30nm when it was not loaded with drugs. Then 30 hydrophobic drugs were selected for testing, of which 13 drugs had a drug loading rate greater than 40%, and 30 drugs had a drug loading rate greater than 20%, and the drug loading efficiency was much higher than that of traditional PEG-PDLLA, PEG-PCL and PEG-PLGA.
[0156] Test Example 3 Drug compatibility of block polymer PEG-PBuSEA containing sulfoxide structure
[0157] Inspired by the universal solvent properties of dimethyl sulfoxide, the sulfoxide structure has excellent compatibility with many compounds, and the drug loading of micelles is affected by this compatibility. Dissolve 1.5 mg of paclitaxel (PTX) in 10 μL of dimethyl sulfoxide, then add 500 μL of blank micelles (PEG-PBuSEA, PEG-PDLLA) and mix by pipetting. The results are shown in Figure 2. Figure 6 As shown, Figure 6 Figure 1 is a characterization diagram of the compatibility of PEG-PBuSEA and PEG-PDLLA with drugs. Figure 6 It can be seen that PEG-PBuSEA, with its liquid core and good drug-polymer compatibility, can load the PTX that has formed aggregates into the micelles to obtain a clear drug-loaded micelle solution. However, due to its poor compatibility with drugs, the traditional carrier PEG-PDLLA has drug-drug interaction > drug-polymer compatibility, PTX is always in an aggregate state, the drug cannot be loaded into the micelles, and a large amount of drug precipitation is obtained after centrifugation. It can be seen that PEG-PBuSEA has good compatibility with drugs.
[0158] Test Example 4 Characterization of Stability of Block Polymer PEG-PBuSEA Drug-Loaded Micelle Containing Sulfoxide Structure
[0159] The stability of drug-loaded micelles is one of their important properties. The aggregation of drug-loaded micelles will have a significant impact on their efficacy and function. Therefore, the stability of drug-loaded micelles under different conditions was measured in vitro.
[0160] Take MZ1 and PTX as examples for determination. Take 1 mg PEG-PBuSEA, add the corresponding amount of drug, rotary evaporate the organic solvent, add 1 mL PBS or different contents of fetal bovine serum (FBS), the final FBS content is 0, 10%, 50% or 100%, hydrate at 37°C for 2 minutes, 120W probe ultrasound for 1 minute, 5000g centrifugation to remove aggregated particles, and the final concentration of drug-loaded micelles is 1 mg / mL. PEG-PDLLA was selected as the control, and drug-loaded micelles were prepared in the same way. The particle size of the drug-loaded micelles was measured by DLS at different time points, and the drug-loaded micelles were placed in a 37°C constant temperature incubator after measurement.
[0161] The results are as follows Figure 7 As shown, Figure 7 The stability characterization diagram of PEG-PBuSEA and PEG-PDLLA encapsulating paclitaxel and MZ-1, Figure 7 In the figure, a is the curve of particle size change of PEG-PBuSEA@MZ1 in different buffer media over time, b is the photo of PEG-PBuSEA@MZ1 in different buffer media and time points, c is the curve of particle size change of PEG-PBuSEA@PTX and PEG-PDLLA@PTX in different buffer media over time, d is the photo of PEG-PBuSEA@PTX and PEG-PDLLA@PTX in different buffer media and time points. Figure 7 It can be seen that the particle size of PEG-PBuSEA@MZ1 in PBS does not change much within 48 hours and remains basically stable; in the presence of serum, the particle size of PEG-PBuSEA@MZ1 remains basically unchanged within 24 hours, but the particle size increases slightly when the time is extended to 48 hours, indicating that there is a small amount of aggregation of drug-loaded micelles. The stability of PEG-PBuSEA@PTX was measured with commercial PEG-PDLLA@PTX as a control. The particle size of commercial drug-loaded micelles PEG-PDLLA@PTX increased significantly after being placed in PBS and 10% FBS for 12 hours, and obvious drug precipitation was visible to the naked eye; while PEG-PBuSEA@PTX can remain stable within 36 hours when the drug loading is higher than PEG-PDLLA@PTX, and no drug aggregation is observed, indicating its good stability at 37°C.
[0162] Test Example 5 Safety Evaluation of Block Polymer PEG-PBuSEA Containing Sulfoxide Structure
[0163] The safety of PEG-PBuSEA as a drug delivery carrier requires more in-depth research to ensure its safety in clinical applications. Therefore, the in vitro cytotoxicity of PEG-PBuSEA was evaluated by CCK-8.
[0164] 3T3, 293T, HCT116, MDA-MB-231 and Raw264.75 cell lines were selected, and the cells with good growth status were digested and seeded in 96-well plates at appropriate density and cultured overnight. After the cells adhered to the wall, different concentrations of PEG-PBuSEA were added. After the 96-well plate was placed in a cell culture incubator for 48 hours, 10 μL CCK-8 was added to each well, incubated at 37°C for 1 hour, and the absorbance was measured at 450nm using an enzyme reader.
[0165] The results are as follows Figure 8 As shown, Figure 8 Figure 5 is a graph showing the cytotoxicity of PEG-PBuSEA in Test Example 5. Figure 8 It can be found that for 3T3, 293T, HCT116, MDA-MB-231 and Raw264.7, even the addition of 4 mg / mL PEG-PBuSEA did not show obvious cytotoxicity, indicating that it has good safety and biocompatibility.
[0166] Test Example 6 Construction of MDA-MB-231 subcutaneous tumor model and evaluation of tumor inhibition effect
[0167] The well-growing MDA-MB-231 cells were digested, washed twice with PBS, and resuspended to prepare a cell suspension of 10 million per milliliter. The suspension was subcutaneously injected into the left armpit of female BALB / c nude mice (6-8 weeks old), 100 μL per mouse, i.e., 1 million cells. When the tumor grew to 100 cubic millimeters, the drug was administered by tail vein injection. The drug was paclitaxel encapsulated in PEG-PBuSEA. The paclitaxel dose was 15 mg / kg, and the PEG-PBuSEA dose was 150 mg / kg.
[0168] The results are as follows Fig. 9 As shown, Fig. 9 The figure below shows the tumor inhibition effect of PEG-PBuSEA@PTX drug-loaded micelles in a mouse triple-negative breast cancer (MDB-MA-231) subcutaneous tumor model. The left figure shows the tumor growth curve, and the right figure shows the tumor weight analysis at the end of the experiment. Fig. 9 It can be seen that after four administrations, PEG-PBuSEA loaded with paclitaxel (PTX) can effectively inhibit the growth of MDA-MB-231 subcutaneous tumors, and the final average tumor volume is less than 100 cubic millimeters, showing an excellent tumor inhibition effect.
[0169] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A block polymer containing a sulfoxide structure, characterized in that: It has the structure shown in formula I: In formula I, n is 5 to 100, m is 20 to 500, R1 is hydrogen or methyl, and x is 1 to 8; The structure of the block polymer containing a sulfoxide structure also includes a residue from a chain transfer agent.
2. The block polymer containing sulfoxide structure according to claim 1, characterized in that In formula I, R1 is hydrogen.
3. The block polymer containing a sulfoxide structure according to claim 1 or 2, characterized in that The specific structure is shown in Formula I-1:
4. The method for preparing a block polymer containing a sulfoxide structure according to any one of claims 1 to 3, characterized in that: The following steps are involved: The first reaction is carried out between mercaptoethanol and 1-bromobutane to obtain a compound represented by Formula 1; The compound represented by Formula 1 is subjected to a second reaction with the compound represented by Formula 2 to obtain an acrylic acid ester-containing thioether monomer represented by Formula 3; The acrylate-containing thioether monomer and hydrogen peroxide are subjected to a third reaction to obtain an acrylate-containing sulfoxide monomer as shown in Formula 4; The sulfoxide monomer containing acrylate is subjected to free radical polymerization reaction under the action of polyethylene glycol macromolecular chain transfer agent to obtain the block polymer containing sulfoxide structure.
5. The preparation method according to claim 4, characterized in that: The reagents for the first reaction also include a first acid binding agent and a first organic solvent; The first acid binding agent includes one or more of potassium carbonate, triethylamine, N,N-diisopropylethylamine and pyridine; The first organic solvent includes one or more of acetonitrile, dichloromethane and chloroform; The molar ratio of the 1-bromobutane to the mercaptoethanol is 1 to 1.5:1; The molar ratio of the first acid binding agent to mercaptoethanol is 1 to 2:1; The temperature of the first reaction is room temperature and the time is 12 to 24 hours.
6. The preparation method according to claim 4, characterized in that: The reagents of the second reaction also include a second acid binding agent and a second organic solvent; The second acid binding agent includes one or more of triethylamine, N,N-diisopropylethylamine and pyridine; The second organic solvent includes one or more of diethyl ether, dichloromethane and chloroform; The molar ratio of the compound represented by Formula 2 to the compound represented by Formula 1 is 1 to 1.5:1; The ratio of the amount of the second acid binding agent to the compound represented by Formula 1 is 1 to 2:1; The temperature of the second reaction is room temperature, and the time is 2 to 24 hours.
7. The preparation method according to claim 4, characterized in that: The reagents for the third reaction also include a catalyst and a third solvent; The catalyst includes molybdenum dioxide dichloride; The third solvent includes one or more of acetonitrile, acetone and water; The molar ratio of the catalyst to the sulfide monomer containing acrylate is 0.01 to 0.1:1; The molar ratio of the hydrogen peroxide to the acrylate-containing thioether monomer is 1 to 1.1:1; The temperature of the third reaction is room temperature, and the time is 20 to 60 minutes.
8. The preparation method according to claim 4, characterized in that: The polyethylene glycol macromolecular chain transfer agent includes a compound having a structure shown in Formula 5: The reagents for the free radical polymerization reaction also include a free radical initiator and a fourth organic solvent; The free radical initiator includes azo initiators, organic peroxide initiators and inorganic peroxide initiators; The fourth organic solvent includes N,N-dimethylformamide, dioxane or dimethyl sulfoxide; The molar ratio of the acrylate-containing sulfoxide monomer to the free radical initiator is 1:0.0025-0.1; The molar ratio of the acrylate-containing sulfoxide monomer to the polyethylene glycol macromolecular chain transfer agent is 1:0.01-0.2; The temperature of the free radical polymerization reaction is 60-80° C., the time is 6-24 hours, and the free radical polymerization reaction is carried out in anhydrous and oxygen-free state.
9. Use of the block polymer containing a sulfoxide structure according to any one of claims 1 to 3 or the block polymer containing a sulfoxide structure obtained by the preparation method according to any one of claims 4 to 8 in solubilizing hydrophobic drugs and preparing hydrophobic drug carriers, characterized in that: The oil-water partition coefficient of the hydrophobic drug is greater than 2, and the molecular weight of the hydrophobic drug is 150-1500.
10. A drug-loaded micelle, characterized in that: The block polymer containing a sulfoxide structure according to any one of claims 1 to 3 or the block polymer containing a sulfoxide structure obtained by the preparation method according to any one of claims 4 to 8 and a hydrophobic drug are prepared by a thin film dispersion method, a nanoprecipitation method or a microfluidics method.
